2017
DOI: 10.1093/eurpub/ckx109
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of chronic respiratory diseases and associated factors in the adult Italian population

Abstract: Italian adults with CRDs are more likely to be exposed to aggravating factors but are also knowledgeable of their condition and amenable to behaviour change. Since effective interventions for modifying these factors are available, there is an opportunity to reduce the significant disease burden of CRDs through specifically targeted health promotion interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The study characteristics of the included studies are summarized in Table 2. In total, we included 27 studies published since 2011, except for one study that published in 1996: twelve from Europe [10, 12, 13, 16, 17, 20, 23, 25, 2830, 35], nine from the North America (United States and Canada) [11, 15, 18, 21, 26, 27, 3234], three East Asia (China and Korea) [19, 22, 36], three from the Latin America and 6 low- and middle-income countries and Australia [14, 24, 31]. The majority of the included studies were published after 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The study characteristics of the included studies are summarized in Table 2. In total, we included 27 studies published since 2011, except for one study that published in 1996: twelve from Europe [10, 12, 13, 16, 17, 20, 23, 25, 2830, 35], nine from the North America (United States and Canada) [11, 15, 18, 21, 26, 27, 3234], three East Asia (China and Korea) [19, 22, 36], three from the Latin America and 6 low- and middle-income countries and Australia [14, 24, 31]. The majority of the included studies were published after 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The epidemiology and disease burdens of CRDs vary substantially worldwide. Previous studies have estimated the prevalence of CRDs at the regional or national level but not at the global level [3][4][5]. Understanding the prevalence and incidence trends of CRDs is vital for improving the control and prevention of CRDs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that respiratory disease is one of the main disorders that require intensive care, and that the prognosis is poor in patients admitted to ICU due to various respiratory diseases [8][9][10][11][12][13]18,19]. The incidence and proportion of respiratory disease in the community has been increasing in recent years because of the increasing aging population, excessive body weight due to westernization, increased morbidity of chronic pulmonary disorders, and long-term air pollution exposure [20][21][22]. In our study, the percentage of critically ill patients with respiratory disease as the main cause of ICU admission increased annually.…”
Section: Discussionmentioning
confidence: 99%